2012
DOI: 10.1111/j.1464-410x.2012.11580.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the sexual side effects of finasteride as related to hand preference for men undergoing treatment of male pattern baldness

Abstract: E 2 2 1What ' s known on the subject? and What does the study add? Cerebral lateralization/specialization is a neurophysiological feature that has been documented regarding somatic, psychological and sexual functioning and that may be manifested in differences in hand preference, cognitive style, gonadal hormonal effects and possibly even sexual orientation. In this study we investigated a possible cerebral lateralization effect on sexual response for dihydrotestosterone, using fi nasteride as a hormone-blocki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
3
6
2
Order By: Relevance
“…In order to be directed toward one or to the other neuroendocrine axes (left or right hemibrain), peripheral inputs need to be acted upon by different neuromodulators such that a modulator channeling information toward one axis would not do so toward the other. Indeed, distinct antiandrogenic compounds act exclusively on either one or the other neuroendocrine axes, as demonstrated in previous studies with bicalutamide and finasteride (Motofei et al, , 2013, and now confirmed by the current results with tamoxifen. In our sample, tamoxifen decreased sexual function more in left-handed men, suggesting that the specific relationship between sexual function and estrogens in these men is generally different from that of right-handed men, an effect possibly due to differential processing of visual/sexual information by these two groups.…”
Section: Contextual Interpretationsupporting
confidence: 86%
See 3 more Smart Citations
“…In order to be directed toward one or to the other neuroendocrine axes (left or right hemibrain), peripheral inputs need to be acted upon by different neuromodulators such that a modulator channeling information toward one axis would not do so toward the other. Indeed, distinct antiandrogenic compounds act exclusively on either one or the other neuroendocrine axes, as demonstrated in previous studies with bicalutamide and finasteride (Motofei et al, , 2013, and now confirmed by the current results with tamoxifen. In our sample, tamoxifen decreased sexual function more in left-handed men, suggesting that the specific relationship between sexual function and estrogens in these men is generally different from that of right-handed men, an effect possibly due to differential processing of visual/sexual information by these two groups.…”
Section: Contextual Interpretationsupporting
confidence: 86%
“…In contrast, previous studies suggest predominantly androgen-based sexual activation in right-handed men (Motofei et al, 2013). In order to understand the interrelation among sexual hormones and hand preference, we provide further contextual interpretation of the results taking into account the relevant literature data.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…We have already performed a study in this regard (s3, s4) that confirmed the previous expectation regarding hand preference (2), but the number of homosexual participants in our sample was too small. [6] Thus, we believe a larger study including many participants, a significant number of whom are homosexual men should help clarify (inter) relationships among sexual orientation, hand preference and finasteride adverse effects.…”
Section: How To Test the Hypothesissupporting
confidence: 80%